Busway distribution system-sizing and planning aspects for automotive weld shop - Sana Zaheer; Raja Masood Larik (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Resistance spot welding with its characteristic “dirty electrical load” is adistinctive engineering problem. The wide range of its industrial applications has made the subject an exciting research domain. Owing to the in term it tence of a welding operation, random overlapping of welding pulses, its sensitivity to voltage variation and application-specific quality control requirements, the electrical distribution system for welding loads need to be tied strongly with the process-related requirements. One of the most important applications of resistance welding is an automotive body shop, also called weld shop. This is where various units of a car body are welded together to form a shell that begins to look like a car. This paper focuses on explaining the nature of welding load and process requirements of a weld shop, leading towards the design and development of a Microsoft Excel based tool for optimal sizing of high current busway distribution system for resistance spot welding machines.This tool can be effectively used as a desktop application for efficient design development and comprehension of various design criteria. Besides, numerical based calculations have been provided with sound reasoning, progressively developing the proposed design criteria.